Análisis comparado del hábeas corpus en Bolivia, Colombia y Ecuador (Tema Central) - Pinos Jaén, Camilo Emanuel (2022)
This research addresses the current state of habeas corpus in Ecuador and Colombia, as well as the liberty action in Bolivia, established as a right and jurisdictional guarantee. Considering its evolution throughout history, a chronological route of Rome, England, Spain and in some Latin American countries was carried out in order to understand the need for its recognition in the legal system of each State. To this end, after identifying its constitutional recognition, the object, scope of protection and procedural reality were analyzed on the basis of the study of the legal provisions and norms of each State; as well as, the development of its highest constitutional justice administration bodies, also known as the closing bodies in the mater. In this sense, it was possible to recognized the rights that are mainly protected through this guarantee, such as freedom of movement, physical integrity, and life; however, there are related rights such as health and dignity, for example, that are also protected, which varies according to the state under analysis. Finally, in addition to establishing similarities and differences, it was possible to find some problems and challenges of habeas corpus and action for liberty, which, in a certain way, limit greater effectiveness in practice.